2012
DOI: 10.1007/s00268-012-1750-6
|View full text |Cite
|
Sign up to set email alerts
|

Trauma during Pregnancy: A Population‐based Analysis of Maternal Outcome

Abstract: Trauma during pregnancy, whether minor or severe, is associated with unfavorable maternal outcomes. Injuries considered minor for the general population are not minor for pregnant women. Therefore, these patients should be monitored carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 27 publications
3
31
1
1
Order By: Relevance
“…Trauma appears to be incident in our study to an extent of 5.84% which is in consistency with the findings of Choudhary et al (4.02%) and Colleman et al (7%) [12,4]. Cheng et al reported severe abdominal trauma to be associated with 6 fold increase in AP [25]. Dahmus and Sibai reported that 1.5% -9.4% of all cases of AP occur due to abdominal trauma [26].…”
Section: Discussionsupporting
confidence: 82%
“…Trauma appears to be incident in our study to an extent of 5.84% which is in consistency with the findings of Choudhary et al (4.02%) and Colleman et al (7%) [12,4]. Cheng et al reported severe abdominal trauma to be associated with 6 fold increase in AP [25]. Dahmus and Sibai reported that 1.5% -9.4% of all cases of AP occur due to abdominal trauma [26].…”
Section: Discussionsupporting
confidence: 82%
“…Placental abruption is strongly associated with preeclampsia and this complication may account for up to 50% of cases. However, it may also be related to other causes, such as smoking and trauma . In this study, the high incidence and severity of this bleeding condition were shown.…”
Section: Discussionmentioning
confidence: 51%
“…The increased risk of SMO with increasing maternal age and parity is well‐known. It is known that age and multiparity are also strongly associated with the occurrence of placental abruption and abnormally invasive placenta, along with various other morbid conditions during pregnancy and labor . The association between previous cesarean sections and hemorrhage is also known.…”
Section: Discussionmentioning
confidence: 99%
“…11 Most severe maternal injuries were reported to lead to adverse pregnancy outcomes. 11 Most severe maternal injuries were reported to lead to adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%